The Influence Of Price Consciousness, Brand Image And Celebrity Endorsement Toward Women's Purchase Intention On The Whitening Skincare Group : Indonesian Gen-Y Females - Fitri Novilia; Agus Rahayu; Heny Hendrayati (West Science Journal Economic and Entrepreneurship, 2023)
This study examines the influence of price consciousness, brand image, and celebrity endorsement on purchase intention among women in the whitening skincare segment, focusing on Generation Y women in Indonesia. In the rapidly growing beauty market, particularly in the whitening skincare category, understanding consumer behavior is crucial. The factors of price consciousness, brand image, and celebrity endorsement have become prominent in shaping consumer preferences, especially among Generation Y women. The research aims to explore the relationships between these factors and the purchase intentions of Generation Y women towards whitening skincare products. By delving into the impact of price awareness, brand perception, and celebrity endorsements on purchase decisions, the study seeks to provide valuable insights for the beauty industry. The findings are expected to assist in crafting more effective marketing strategies aligned with the preferences and needs of the Generation Y female consumer market in Indonesia.